Cover Image, Volume 176A, Number 10, October 2018. Issue 10 (31st October 2018) - Campbell, Ian M.; Sheppard, Sarah E.; Crowley, T. Blaine; McGinn, Daniel E.; Bailey, Alice; McGinn, Michael J.; Unolt, Marta; Homans, Jelle F.; Chen, Erin Y.; Salmons, Harold I.; Gaynor, J. William; Goldmuntz, Elizabeth; et al.
Abstract : The cover image is based on the Special Issue Article What's New with 22q? An update from the 22q and You Center at the Children's Hospital of Philadelphia, DOI:10.1002/ajmg.a.40637 . Illustration Credit: Eo Trueblood, Lead Illustrator, Stream Studios: Medical Illustration, The Children's Hospital of Philadelphia.